Insight into the incredible effects of microwave heating: Driving changes in the structure, properties and functions of macromolecular nutrients in novel food - Deng, Xuan; Huang, Haozhou; Huang, Shengjie; Yang, Ming; Wu, Jing; Ci, Zhimin; He, Yanan; Wu, Zhenfeng; Han, Li; Zhang, Dingkun (Frontiers in Nutrition, 2022)
Microwave heating technology performs the characteristics of fast heating, high efficiency, green energy saving and easy control, which makes it deeply penetrate into the food industry and home cooking. It has the potential to alter the appearance and flavor of food, enhance nutrient absorption, and speed up the transformation of active components, which provides an opportunity for the development of innovation foods. However, the change of food driven by microwave heating are very complex, which often occurs beyond people's cognition and blocks the development of new food. It is thus necessary to explore the transformation mechanism and influence factors from the perspectives of microwave technology and food nutrient diversity. This manuscript focuses on the nutritional macromolecules in food, such as starch, lipid and protein, and systematically analyzes the change rule of structure, properties and function under microwave heating. Then, the flavor, health benefits, potential safety risks and bidirectional allergenicity associated with microwave heating are fully discussed. In addition, the development of new functional foods for health needs and future market based on microwave technology is also prospected. It aims to break the scientific fog of microwave technology and provide theoretical support for food science to understand the change law, control the change process and use the change results.